Workshop Peningkatan Kinerja Guru Pendidikan Anak Usia Dini di Desa Duren Kabupaten Karawang - Rukajat, Ajat; Gusniar, Iwan Nugraha; Abas, Totoh Tauhidin (Al-DYAS, 2022)
The theme of this research is the Workshop on Improving the Performance of Early Childhood Education Teachers in Duren Village, Karawang Regency. Is a pre-school educational institution that prepares students to continue to the next level. The development of human resources, in this case educators, is a very decisive factor in encouraging teacher performance so that an increasingly urgent demand to make changes today's innovative performance becomes an increasingly urgent demand to be implemented by teachers. Educators have a very strategic role in the formation of knowledge, skills, and character of students. Therefore, professional educators will carry out their duties professionally so as to produce more qualified students. Becoming a professional educator will not just happen without efforts to improve their abilities. As for one way to realize the competence of educators is the party who has an important role including the principal, where the principal is a very important educational leader.